Iodine salt level at the Krebet Village of Ponorogo - Elmie Muftiana (Jurnal Keperawatan, 2016)
The decrease of iodine salt levels caused the broken from the component of salt. It will be happen when cooking, a wrong cooking process, and a wrong saving way. This study aims to determine iodine salt levels in peoples that have mental retardations at Krebet village, Ponorogo.The study design used descriptive design. with purpossive sampling.The samples is 87 respondents. The tool of data collecting used queistionnaire and observed with Iodine test to know the iodine salt levels. The results of univariate analyzed showed that 51 respondents (58,6%) had good daily iodine salt levels (purple), 9 respondents (10,3%) saved salt in a closed place, 56 respondents (64,4%) consumed daily rough salt, 87 respondents (100%) cooked with water boilling conditions.The results of the study also showed, although peoples has been right when buying the salt, but saving it in a open plastic will make the salt become wet and decrease the iodised salt levels.